2023
DOI: 10.3390/cells12070993
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Alleviates Protein Aggregates, Reduces Neuroinflammation, and Rescues Demyelination in Globoid Cell Leukodystrophy

Abstract: We have shown in vivo and in vitro previously that psychosine causes dysfunction of autophagy and the ubiquitin-proteasome system underlying the pathogenesis of globoid cell leukodystrophy (GLD), a devastating lysosomal storage disease complicated by global demyelination. Here, we investigated the therapeutic efficacy of the mTOR inhibitor rapamycin in twitcher mice, a murine model of infantile GLD, in biochemical, histochemical, and clinical aspects. Administration of rapamycin to twitcher mice inhibited mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, whether mTOR is involved in the astrocyte activation associated with NP remains unknown. Other notable ndings as related to the present study include the observation that an inhibition of mTOR alleviates demyelination and neuroin ammation in globoid cell leukodystrophy [15]. In addition, receptorinteracting protein 3 (RIP3), which is involved in the development and responses to tissue injury, antiviral immunity and many other physiological and pathologic processes [16], induces neuroin ammatory responses after perceived cellular stress [17] and accumulates in reactive astrocytes after spinal cord injury [18].…”
Section: Introductionmentioning
confidence: 76%
“…However, whether mTOR is involved in the astrocyte activation associated with NP remains unknown. Other notable ndings as related to the present study include the observation that an inhibition of mTOR alleviates demyelination and neuroin ammation in globoid cell leukodystrophy [15]. In addition, receptorinteracting protein 3 (RIP3), which is involved in the development and responses to tissue injury, antiviral immunity and many other physiological and pathologic processes [16], induces neuroin ammatory responses after perceived cellular stress [17] and accumulates in reactive astrocytes after spinal cord injury [18].…”
Section: Introductionmentioning
confidence: 76%
“…The presently reported findings of mTOR pathway activation in MLD could underlie both deficient autophagy and inflammation, given mTOR has a key role in regulating inflammation [34]. A recent study in a mouse model of the related condition Krabbe disease demonstrated that inhibition of the mTOR pathway with rapamycin enhanced autophagy, reduced inflammation and attenuated leukodystrophy [35]. These findings are consistent with our observations in Niemann-Pick Type C1, where neurodegeneration was reduced by enhancing autophagy through an effect on NAD levels [17].…”
Section: Discussionmentioning
confidence: 99%
“…58 Rapamycin, an inhibitor of mTOR but autophagy activator, was used in twitcher mice in order to reduce the deposition of insoluble ubiquitinated protein, corroborated with the attenuation of astrogliosis and microgliosis. 59 This therapeutic modality was critical in inducing cortical myelination, neurite density, and rescued the neurological abnormalities of twitcher mice. Further, it induced cell migration and improved the clearance of focal adhesion in GALC-deficient fibroblasts.…”
Section: Therapeutic Approaches For Treatment Of Krabbe Diseasementioning
confidence: 99%